Determination of cerium valent state in solution of CeO₂₋x nanoparticles - Gayduk, O.V. (Functional Materials, 2018)
Determination of different valence forms cerium in solution of CeO₂₋x nanoparticles was performed using spectrophotometric method. Ce(IV) was determined from the reaction of o-tolidine oxidation in sulfuric-acid medium. The total cerium concentration was determined after reducing Ce(IV) by sodium oxalate. In the capacity of reagent, there was used chlorophosphonazo III which formed he complex of the composition of 1:1 with cerium(III). The influence of sodium citrate, the stabilizer of the nanoparticles, in cerium determination, was studied. There were developed reliable and sensitivite echniques for determination of Ce(IV) and the total cerium mass concentrations in the solution of CeO₂₋x nanoparticles. Relative standard deviations at of the cerium determination were found not to exceed 0.05.